2004
DOI: 10.1093/annonc/mdh308
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of failure, prognostic factors and survival in locoregionally advanced head and neck cancer treated with concomitant chemoradiotherapy: a 9-year, 337-patient, multi-institutional experience

Abstract: This analysis suggests that pattern of failure in primary head and neck cancer may be dependent upon treatment strategy. Randomized clinical trials of induction chemotherapy are warranted as a means to determine if a decrease in distant metastases can lead to an increase in survival rates in the setting of effective chemoradiotherapy for locoregional control. Additionally, this analysis provides impetus for randomized clinical trials of organ preservation chemoradiotherapy in sites outside the larynx and hypop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
220
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(229 citation statements)
references
References 31 publications
5
220
0
4
Order By: Relevance
“…[2][3][4] Because current treatment protocols focus primarily on improving locoregional control, further gains in survival may come from improved treatment or the prevention of distant recurrence, second primary cancer, and comorbid medical illnesses. [15][16][17][18] In this article, we demonstrated that with highly effective locoregional therapy delivered by a dedicated multidisciplinary team, head and neck cancer patients now fail mostly at distant disease sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Because current treatment protocols focus primarily on improving locoregional control, further gains in survival may come from improved treatment or the prevention of distant recurrence, second primary cancer, and comorbid medical illnesses. [15][16][17][18] In this article, we demonstrated that with highly effective locoregional therapy delivered by a dedicated multidisciplinary team, head and neck cancer patients now fail mostly at distant disease sites.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the experience of other recent reports. 2,[19][20][21] It is clear that PET/CT imaging detects disease recurrence earlier than expectant management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies on locoregionally advanced SCCHN have been focusing on neoadjuvant chemotherapy (NAC) with a high complete response (CR) rate followed by definitive radiotherapy, or concurrent chemoradiotherapy showing to improve the survival rate and to preserve functions and organs (Pignon et al, 2000;Monnerat et al, 2002;Forastiere et al, 2003;Haddad et al, 2003). However, 20 -30% of advanced patients with a pathologically CR even after the recent aggressive treatment has been showing locoregionally recurrent and/or distant metastatic tumours (unpublished data in our institutes) resulting in the poor outcome nevertheless (Argiris et al, 2004;Brockstein et al, 2004;Cohen et al, 2004). Based on these results, more advanced multidisciplinary treatments should be indispensable in the aim of improving the poor outcome of patients with advanced SCCHN.…”
mentioning
confidence: 92%
“…Показатели выживаемости у них существенно ниже, а прогноз хуже, чем у пациентов с первичными новооб-разованиями. Частота встречаемости рецидивных образо-ваний при плоскоклеточном раке органов головы и шеи колеблется, по данным разных авторов, от 30 до 50% [1,2]. Следует отметить, что терапевтические возможности ле-чения рецидивных злокачественных опухолей существен-но ниже из-за проведенного ранее как самостоятельного лучевого, так и химиолучевого лечения.…”
unclassified